High-risk jejunal gastrointestinal stromal tumor: case report and comparative review of international guidelines - Arias, Francisco C.; Sanchez, Alejandro A.; M. Baez, Yannin; M. Rodriguez, Jesus; L. Martinez , Alexis (International Journal of Research in Medical Sciences, 2025)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal neoplasms of the gastrointestinal tract, arising from interstitial cells of Cajal. Diagnosis and management have advanced through molecular testing, surgery, and tyrosine kinase inhibitors. Although usually seen in older adults, GISTs may occur in younger patients with atypical symptoms. We report a high-risk jejunal GIST and compare major international guidelines to inform management. A literature review and guideline comparison were conducted using recent recommendations from ACG, AGA, ESMO, BSG, ESGE, NICE, JSCO, and the Royal College of Pathologists. These were correlated with the clinical, imaging, surgical, and histopathological findings of a 40-year-old male patient. The patient presented with abdominal distension, obstructive symptoms, and a palpable mass. CT revealed a 14×13×11 cm well-circumscribed mass in the epigastric/mesogastric region. Surgery identified a jejunal tumor 30 cm distal to the ligament of Treitz, requiring en bloc resection and primary anastomosis. Histopathology confirmed a spindle-cell GIST (CD117+, DOG1+, CD34–, Ki-67: 5/50 HPF) with high-risk features. Postoperative recovery was uneventful. Guidelines consistently recommend R0 resection, immunohistochemical confirmation, mutational profiling, and long-term surveillance. Adjuvant imatinib is advised for high-risk disease. This case underscores the need for early recognition and guideline-based management of GISTs, particularly in patients with nonspecific symptoms and large abdominal masses. International concordance emphasizes imaging, endoscopic ultrasound with biopsy, immunohistochemistry, and molecular testing for risk stratification. Surgery remains the cornerstone of treatment, with adjuvant therapy in high-risk cases. Multidisciplinary care is essential to optimize outcomes.